Validation of the San Diego Early Test Score for Early Human Immunodeficiency Virus Infection Among Amsterdam Men Who Have Sex With Men. (10th September 2019) - Dijkstra, Maartje; Lin, Timothy C; de Bree, Godelieve J; Hoenigl, Martin; Schim van der Loeff, Maarten F
Abstract: The San Diego Early Test score is a simple risk-assessment tool for acute, and early human immunodeficiency virus (HIV) infection. Validation in a prospective cohort of Amsterdam men who have sex with men showed fair prediction of HIV seroconversion (AUC, 0.701). This score can help prioritize and target HIV-prevention strategies.